EMPOWERING FUTURE CREATIVES: A COMMUNITY ENGAGEMENT PROGRAM ON ILLUSTRATION IN THE INDUSTRY FOR QUALITY EDUCATION - Nabila Shabiriani, Uzda; Ulinnuha, Muhammad Khirzan; Dirgantara, Satrya; Manalu, Daniella Oktalina (Bina Nusantara University, 2025)
To the increased need for illustrators in the creative sector, Community Engagement Program on Illustration in The Industry for Quality Education came up with the Empowering Future Creatives program. It impacted 39 emerging creatives and tertiary learners to continue studying about illustration using webinars, seminars, and collaboration spaces that used experiential learning. The students were also able to experience significant parts of professional illustration, including the ideation process, storytelling, and business involved in the career. The students were also directly exposed to industry professionals who served as mentors and provided educative information regarding the industry. The evaluation process indicated a high degree of interaction because 92% of the participants cited an impact on their own professional development. 85% Students developed their illustration capabilities, and 59% attained internships, freelance jobs, or post-course education because of the scheme. As well as technical competency, the program developed the students' professional network far more significantly and gave them far more industry problem awareness and knowledge of career management strategies. The program also addressed the above-mentioned issues regarding the perception of illustration as an unprofessional practice, highlighting the need for greater awareness of its role in visual communication, marketing, and branding. The course raises the level of education for the Sustainable Development Goals (SDGs) through experiential and systematic learning. It also reaffirms illustration's creative and business legitimacy as a career, thereby enabling draftsmen to get the exposure and recognition they deserve within the industry.